UPAYA KEPOLISIAN RESOR HALMAHERA UTARA DALAM MENANGGULANGI KEJAHATAN NARKOTIKA KABUPATEN HALMAHERA UTARA - Ernest Sengi (Universitas Kristen Satya Wacana, 2019)
The territory that is directly facing the pacific ocean and surrounded by small islands becomes a potential target for receiving narcotics in North Halmahera. This paper discusses a legal issue about the role of the North Halmahera Police in overcoming narcotics crimes in their region. In order to answer the legal issue, a sociological approach and a statute approach were used. These approaches are appropriate for assessing the role of the North Halmahera Police in tackling narcotics crimes and to answer whether regulations on drugs has supported the role of the police or not. The result of the research showed that there were 23 suspects who were arrested with 12 narcotics cases. However, the preventive efforts were carried out through patrols and raids on hangouts, vehicles, and narcotics hazard awareness socialization. It is found that some inhibitors of narcotics crime law enforcement exist in North Halmahera: first, the number of police personnel only reached 25 people with 2 investigators; second, another problem came from inadequate facilities issue; third, information leakage often occurred before raids were carried out.